HOMILETIKA AL-QUR’AN REFLEKSI ATAS PEMIKIRAN GABRIEL SAID REYNOLDS - Zulhamdani Zulhamdani (UIN Sunan Gunung Djati Bandung, 2023)
This writing discusses the concept of Quranic homiletics proposed by Gabriel Said Reynolds through a literary and intertextual study approach. He views the conversation between the Quran and the Bible as a form of Quranic homily in producing its own religious messages based on the Biblical literature it alludes. This idea is a response to the main stream study of the Quran which tends to rely on the Prophet Muhammad's biography and commentaries to understand the Quran. This approach posits that Muhammad learned from Jewish and Christian figures around him when compiling the Quran. Through a historical-philosophical and descriptive-interpretive approach, this study ultimately concludes that there are indications in the Quran that suggest its initial audience was familiar with Biblical narratives. Therefore, the concept of Quranic homiletics has reason to connect the Quran with pre-Quranic literature. However, viewing the Quran as a homily on Biblical literature would narrow the rich and complex content of the Quran. Furthermore, the independence of the Quran would also be limited under the umbrella of pre-Quranic literature which is considered speculative subtext.